The influence of training on detecting lying in language: a case study of native speakers of Polish using english as a learned language = Wpływ treningu na wykrywanie kłamstwa w języku: Studium przypadku natywnych mówców języka polskiego posługujących się językiem angielskim jako językiem nabytym - Kuzio, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author of the article discusses the importance of detecting dishonesty in various cultures and presents the nature of dishonesty and its problematic assessment. The aims and the hypothesis tested in this study result from the analyses of foreign language learning. In the first part of the article, the author aims to introduce theoretical aspects of detecting lying, its nature, and the research results on the role of the basic factors in the lying process: training, trust, observers, language and culture, and their effectiveness in detecting lying. The study results are presented in the empirical part. The results are analysed in three stages, following the stages of the study being performed and the hypothesis verified. In the final part, the author presents the results showing a correlation between the variables.
Keywords: lying in language; role of lying; role of a foreign language in lying; kłamstwo w języku; rola kłamstwa; rola języka obcego w kłamstwie